Characteristics of Moderate Da'wah in The View of Abdul Mun'im - Edlyn, M. Keanu Zimran; Apriliani, Yola; Fuada, Nadiya; Bono, Shafa Ajeng Prameswari; Sari, Hilda Rara (TATHO: International Journal of Islamic Thought and Sciences, 2024)
The purpose of this study is to identify the characteristics of moderate Islamic da'wah in the view of H. Abdul Mun'im. This qualitative study uses an analytical-narrative approach. The values of wasathiyah Islamic teachings become the theory of analysis of the subject matter of the study. Research data were obtained through observation techniques on Youtbue content about Ustadz H. Abdul Mun'im's da'wah entitled "Dakwah Wasathiyah" on the Tawaf TV Channel. Meanwhile, data analysis goes through the stages of data reduction, presentation, and verification. This study concludes that there are dimensions of wasathiyah Islamic values in the perspective of H. Abdul Mun'im in describing moderate Islamic preaching, including the value of tasamuth in preaching that respects differences in dialogue between religions and mass organizations. Then, the value of tawazun in da'wah that prohibits issues of extremism and gender discrimination. Furthermore, the value of tawasuth in da'wah that prohibits conflicts between mazhab differences and terrorism. The findings of this study confirm that the mainstreaming of moderate Islamic da'wah in Indonesia can be internalised through digital da'wah activities. The limitations of this study have not identified the concrete form of H Abdul Mun'im's moderate Islamic da'wah in the community.